Unexpected complexity of the Embioptera (Insecta) fauna of the Tuscan Archipelago (Italy), with the disambiguation of two species of Haploembia Verhoeff, 1904 and description of a new species of Embia Latreille, 1825 - Fontana, Paolo; Forbicioni, Leonardo (Zootaxa, 2024)
Very little is known about the Embioptera of the Tuscan Archipelago, and no specific study has been published from there on this insect order. The study of literature and new material has allowed us to identify the presence of four species of Embioptera in the Tuscan Archipelago: Haploembia solieri (Rambur, 1842), Haploembia tarsalis Ross, 1940 (which was reported for the first time in Italy), Embia ramburi Rimsky-Korsakov, 1905 and E. ilvana n. sp., which is described here. As regards the species of the genus Haploembia Verhoeff, 1904, some bio-ethological aspects and the global distribution of the two species present in the archipelago are discussed.